Stress and Work-Life Balance of School Teachers: A Social Work Intervention - P., Mythili; G. F., Alban (Journal of Social Work Education and Practice, 2023)
The study is conducted with the teachers of St. Claret Matriculation Higher Secondary school in Thiruvallur District of Tamilnadu. Around 20 samples were collected with the objective of finding out the mental well-being of school teachers. The scientific tool is used for data collection and analysis of collected data. The methodology adopted for conducting the study also mentioned. This paper provides the statistical information on stress and work-life balance of teachers which influences the mental well-being of teachers. Teachers are instruments of the proper and effective education system. Their role plays an importance in academic performance, personality construct, social behavior of students. Mental health of teachers plays a vital role in the professional performance of teachers. Because of this demanding profession, nowadays teachers were facing lots of stress and low level of work-life balances. By addressing these issues by interventions and individual healthy habits can bring positive change in the mental health of teachers.